PENINGKATAN HASIL BELAJAR KOGNITIF DENGAN MENGGUNAKAN MODEL VALUE CLARIVICATION TECHNIQUE (VCT) BERBASIS PENANAMAN NILAI KARAKTER PADA PESERTA DIDIK DI SEKOLAH DASAR - Dian Meilani; Donci Missa (Program Studi Pendidikan Guru Sekolah Dasar-Universitas Muhammadiyah Kupang, 2023)
The low learning outcomes of students at SDN Oeba 2 Kota Kupang Theme 7 The Beauty of My Country's Diversity is a concern for researchers to find solutions to solving these learning problems. This problem is due to the inaccuracy of choosing a learning model that is in accordance with the material in theme 7. To overcome this problem, it is necessary to use an appropriate innovative model, one of which is the Value Clarification Technique (VCT). This study aims to determine the increase in cognitive learning outcomes by using the Value Clarification Technique (VCT) model. This research is a classroom action research with the model used is Kemmis and Mc Taggart which consists of planning, implementing, observing and reflecting, and takes place in two cycles. The subjects of this study were 25 class IV students at SDN Oeba 2, Kupang City. Data collection used the non-test method in the form of observation sheets and the test method in the form of objective tests. Data were analyzed using descriptive qualitative to determine the increase in learning outcomes. The results showed that there was an increase between cycles of 20%, where cycle I (72%) and cycle II (92%). This shows that using the Value Clarification Technology model can improve cognitive learning outcomes.